School Literacy Movement and Parents’ Motivation on EFL Students’ Reading Interest - Juliari, I Gusti Ayu Indah Triana; Susila, I Komang Dedik; Juliani, Ni Putu (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
This research aims to determine partial and simultaneous positive and significant positive effects between the school literacy movement and parents’ motivation together on the reading interest. This type of research was ex post facto. The population of this research was 251 students and the sample was 70 students determined using random sampling technique. Data collection techniques using questionnaires and non-tests. The data were analyzed quantitatively using multiple regression tests, namely t-test and F-test. However, before the implementation of multiple regression tests, the prerequisite tests were implemented (the normality test, multicollinearity test, and heteroscedasticity test). The finding shows that school literacy movement and parents’ motivation have positive and significant effects on reading interest. It can be concluded that the school literacy movement and parents’ motivation affected the students' reading interests. The school and parents should empower the quality of the school literacy movement and parents’ motivation to improve students’ reading interests.